Grappleria corona gen. et sp. nov. (Platyhelminthes: Rhabdocoela: Jenseniidae fam. nov.) and an updated molecular phylogeny of 'dalyelliid' and temnocephalid microturbellarians. Issue 3 (19th April 2021) - Van Steenkiste, Niels W. L.; Rivlin, Natalie; Kahn, Penelope; Wakeman, Kevin; Leander, Brian S.
Abstract : Species of rhabdocoels within the family Dalyelliidae (Platyhelminthes) generally inhabit fresh water and are rare in marine and brackish environments. Here we describe a new species of marine dalyelliid, Grappleria corona gen. et sp. nov., from the Pacific coast of British Columbia. Based on the distinctive morphology of its male copulatory organ and a thorough comparison of traits in all known species of marine and brackish water dalyelliids, we place this new species in a genus of its own. Phylogenetic analyses inferred from rRNA gene sequences derived from G. corona gen. et sp. nov., other representatives of the Dalyelliidae and the closely related Temnocephalida, provide justification for an updated taxonomic classification of these groups. In light of these molecular phylogenetic data, we establish the new family Jenseniidae fam. nov. to encompass genera previously considered dalyelliids but are found only in marine and brackish environments; the composition of the Dalyelliidae sensu novo now contains only freshwater genera. We also classify all temnocephalids into one family and into several subfamilies in order to reflect our improved understanding of rhabdocoel phylogeny. http://www.zoobank.org/urn:lsid:zoobank.org:pub:9DA178AE-5038-4379-AAA1-BEE19565FEF6